Pengaruh Penyimpanan Terhadap Profil Formaldehida Alami dan Kemunduran Mutu pada Ikan Beloso (Saurida tumbil) - Umi Anissah; Giri Rohmad Barokah; Farida Ariyani (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2019)
Greater lizardfish (Saurida tumbil) is known to contain endogenous formaldehyde content. Formaldehyde can kill spoilage bacteria, pathogens, and molds. However, this compound is also carcinogenic. The present research was conducted to determine the profile of endogenous formaldehyde and deterioration in the quality deterioration of greater lizardfish during frozen storage. The sample was provided from TPI Cituis, Tangerang, Banten. Sampling and analysis to determine the formaldehyde profile and fish deterioration were conducted once in a month for four months. The samples were then analyzed for formaldehyde profiles (formaldehyde, TMA, TMAO, and DMA) and quality deterioration profiles (TVB-N, acidity, TPC, and organoleptic plates). The results showed that greater lizardfish had 8.62±3.4 ppm formaldehyde content, which increased in the first-month storage and then decreased in subsequent months. The content of TMA and TMAO increased during frozen storage. Greater lizardfish quality deterioration analysis during storage showed the increasing of TVB-N content. Based on the organoleptic score, greater lizardfish can be stored for up to three months. The pH value and total bacteria of greater lizardfish increased in line with storage time.